Gonad-Sparing Surgical Sterilization in Dogs - Kutzler, Michelle A. (Frontiers in Veterinary Science, 2020)
Elective sterilization of pet dogs is a common surgical procedure performed in veterinary practice. The main benefit of sterilization is population control and the reduction in euthanasia of unwanted dogs. The most common methods for sterilizing female and male dogs are ovariohysterectomy (spay; which removes both the ovaries and the uterus) and castration (neutering; which involves removing the testicles), respectively. However, any surgery that removes the gonads changes the animal in both positive and negative ways. There is mounting evidence supporting the long-term health complications associated with surgical sterilization with gonad removal. Gonads are not merely gamete-producing or ancillary sex/reproductive organs but rather they are necessary endocrine glands for normal metabolic, behavioral, musculoskeletal and anti-neoplastic health. The purpose of this mini review is to describe two gonad sparing surgeries that this author has used to sterilize dogs. These surgeries can be performed on pediatric patients without interfering with pubertal maturation. Dog owners can make the decision when the dog is completely mature whether or not the gonads should be removed.